Role of the corporate sector in earthquake disaster: a case study of Dhaka city - Ferdous, Mushfequa (Department of Architecture, BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2006.